Strategi Pemasaran Islami Dalam Meningkatkan Pendapatan Toko Kue Awana Cupcake Pandan Jaya Kecamatan Geragai - Rahma, Siti; Musthofa, M Arif; Fatimah, Siti (Jurnal Ilmiah Ekonomi Islam, 2024)
The problems in this study are: First, How is the Islamic Marketing Strategy in Increasing Awana Cupcake Revenue. Second, What are the obstacles faced by Awana Cupcake in increasing revenue. This type of research is using qualitative research with a descriptive approach. The type of data collected in this study consists of primary data and secondary data. This research was conducted at Awana Cupcake Pandan Jaya, Geragai District. Data collection techniques are carried out through observation and interviews as well as documentation methods that have to do with the title. The data analysis technique used is qualitative and descriptive analysis. Based on the results of the discussion and analysis, the conclusions are obtained: first, How the marketing strategy in increasing Awana Cupcake's income is focused on its products, where the products offered by Awana Cupcake cake shops are in demand by many people. Second, What are the obstacles faced by awana cupcake in increasing the revenue of awana cupcake cake shop, the solution is to create a distinctive characteristic unit and different flavors and affordable prices.